Effects of physical exercise on Chinese college students’ learning fatigue: the chain mediating role of psychological capital and achievement motivation - Zhao, Hongbo; Huang, Hongxin (Frontiers in Psychology, 2025)
IntroductionLearning fatigue has become increasingly prominent among Chinese college students under intense academic competition and educational “involution,” which threatens their mental health and sustainable academic development. Understanding how physical exercise and positive psychological resources may alleviate learning fatigue is therefore of great practical and theoretical significance in the context of Chinese higher education.ObjectiveTo explore the relationship between physical exercise and learning fatigue among Chinese college students, as well as the relationship between psychological capital and achievement motivation.Research methodA questionnaire survey was conducted on 502 Chinese college students (54.8% male and 45.2% female) using the Physical Exercise Rating Scale, Learning Fatigue Rating Scale, Psychological Capital Scale, and Achievement Motivation Scale. SPSS 27.0, PROCESS 3.4 plugin, and Bootstrap method were used to analyze the data and test the chain mediation effect of psychological capital and achievement motivation.ResultThe direct impact value of physical exercise on college students’ learning fatigue is −0.008, and the impact values of psychological capital and achievement motivation between physical exercise and college students’ learning fatigue are −0.003 and −0.002, respectively. The chain mediation effect of psychological capital and achievement motivation is significant, with an effect value of −0.001.Conclusion(1) Physical exercise can significantly positively predict psychological capital and achievement motivation, and significantly negatively predict learning fatigue; (2) The direct and indirect effects of physical exercise on college students’ learning fatigue are significant. Physical exercise can significantly predict college students’ learning fatigue through the independent mediating effect of psychological capital and achievement motivation, as well as through the chain mediating effect of psychological capital and achievement motivation.